2007
DOI: 10.1177/1077558707305410
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Enhance Breast Cancer Screening, Diagnosis, and Treatment among Racial and Ethnic Minority Women

Abstract: The authors conduct a systematic review of the literature to identify interventions designed to enhance breast cancer screening, diagnosis, and treatment among minority women. Most trials in this area have focused on breast cancer screening, while relatively few have addressed diagnostic testing or breast cancer treatment. Among patient-targeted screening interventions, those that are culturally tailored or addressed financial or logistical barriers are generally more effective than reminder-based intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 81 publications
(94 reference statements)
4
94
0
Order By: Relevance
“…Furthermore, mammography is now an important tool for the detection of early stages of breast cancer (Smith et al, 2003;Adibelli et al, 2009) and thus has a large influence on breast cancer stage at presentation (Dalton et al, 2006;Masi et al, 2007;Pasick et al, 2008). Previous studies have found that the implementation rate of mammography is closely related to income level: people with lower incomes have lower mammography implementation rate (Ward et al, 2008;Cunningham et al, 2009), which suggests that these patients have a higher risk of presentation with a larger, more advanced stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mammography is now an important tool for the detection of early stages of breast cancer (Smith et al, 2003;Adibelli et al, 2009) and thus has a large influence on breast cancer stage at presentation (Dalton et al, 2006;Masi et al, 2007;Pasick et al, 2008). Previous studies have found that the implementation rate of mammography is closely related to income level: people with lower incomes have lower mammography implementation rate (Ward et al, 2008;Cunningham et al, 2009), which suggests that these patients have a higher risk of presentation with a larger, more advanced stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Masi et al reviewed interventions to reduce breast cancer disparities, focusing on screening, diagnostic testing, and treatment (Masi, Blackman, and Peek 2007). Just as Davis et al found an asymmetric distribution of studies on the various aspects of cardiovascular disease disparities interventions ), the majority of interventions addressing breast cancer disparities have focused on breast cancer screening, while relatively few studies have examined interventions to help patients who have an abnormal mammogram or breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%
“…We looked across these reviews and Finding Answers' previous research, [11][12][13][14][15][16][17] and identified several cross-cutting themes. Our findings showed that promising interventions frequently were multi-factorial, targeting multiple leverage points along a patient's pathway of care.…”
Section: Cross-cutting Themesmentioning
confidence: 99%